2011
DOI: 10.1891/1939-2095.4.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioners and Evidence-Based Nursing Practice

Abstract: The objectives of this study were to assess nurse practitioners' (NP) beliefs and attitudes about evidencebased nursing practice (EBNP) and their implementation of EBNP. This exploratory descriptive study surveyed NPs in Tennessee. Most of the respondents were White females, 42 years of age, with a master's degree as a family nurse practitioner (FNP), practicing in primary care for a mean of 7.9 years. The respondents tended to have positive beliefs and attitudes about EBNP, but their implementation of EBNP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 9 publications
1
50
1
1
Order By: Relevance
“…Additionally she agrees that to carry out such intimate tasks such as bed bathing with dignity and without hurting the individual requires great skill, ( Butler (2011) defines the delivery of evidence based practice as the combination of best evidence, nursing expertise, and the inclusion of individuals and their families. Moreover, she goes on to say that inclusion of these factors assumes a positive outcome for the patient, (Butler 2011).…”
Section: Evidence Based Practice Versus Routines and Ritualsmentioning
confidence: 99%
“…Additionally she agrees that to carry out such intimate tasks such as bed bathing with dignity and without hurting the individual requires great skill, ( Butler (2011) defines the delivery of evidence based practice as the combination of best evidence, nursing expertise, and the inclusion of individuals and their families. Moreover, she goes on to say that inclusion of these factors assumes a positive outcome for the patient, (Butler 2011).…”
Section: Evidence Based Practice Versus Routines and Ritualsmentioning
confidence: 99%
“…In a study utilizing nurse practitioner educators, numerous barriers were reported to EBP use, such as resource availability (time/money), oppositional clinical mind set, research training based on research production not utilization, lack of access to data, and lack of mentorship [18] . These factors serve to inhibit maximal implementation of EBP, as well as practice based changes [19,20] . To date, it is not known if ACNP experience the same barriers as other nurses, or to what degree their practice is evidenced based.…”
Section: Two National Published Documents Scope and Standards For Thmentioning
confidence: 99%
“…Nevertheless, studies show the availability of evidence does not always change practice (Butler, 2011; Davidoff et al, 1995; Straus et al, 2011). There is danger in anchoring clinical decisions to just one's own clinical experiences.…”
Section: Why Is Ebp Important To the Busy Np?mentioning
confidence: 99%
“…While EBP does not require the NP to be a statistician, it does require some use of mathematics to estimate items such as: risk of benefit and harm of interventions, determining effect size, and confidence intervals (Straus et al, 2011). The recent study by Butler (2011) on NP attitudes and beliefs about implementing EBP found a majority of respondents identified a lack of knowledge on how to measure clinical outcomes. Many believed it was too difficult (Butler, 2011).…”
Section: Why Is Ebp Important To the Busy Np?mentioning
confidence: 99%
See 1 more Smart Citation